Management of children with cleft lip and palate. - Shah, C. P. (1980)
Cleft lip or palate or both is one of the common congenital conditions in Ontario; its incidence is 1.2 to 1.6 per 1000 live births. A review of the records of 358 patients showed that 40%, particularly those with a severe defect, had other medical problems. This condition can affect the children and their families in many ways. In early life many patients undergo surgical repair and have speech, hearing and dental problems; during adolescence they may have cosmetic, orthodontic and emotional problems. Many parents are concerned about the genetic implications of the defect. This variety of problems requires management by several health care disciplines. Many Canadian health sciences centres offer multidisciplinary team management in a cleft palate clinic. The child's primary care physician, with whom the team exchanges information, plays a significant role in helping the child and the family function optimally.